PERANAN LINGUISTIK TERAPAN DALAM DAKWAH MULTIKULTURAL DI INDONESIA - Bhakti, Wirayudha Pramana (IAIN Pekalongan, 2016)
Dakwah or preaching Islam has a purpose to invite people to consistently perform good deeds and to prevent them from doing evil deeds (amar ma’ruf nahi munkar). However, most of conflicts occur bringing the name of religion, which of those are believed to be caused by the content of the preaching. Often the preaching is conducted in provocative ways and is intolerant with differences. In fact, a good understanding on differences and plurality play a significant role in determining a success of the preaching. Therefore, in order to avoid conflicts bringing the name of Islam, there is a need of preaching which has a comprehensive understanding on differences: multicultural preaching. This type of preaching involves three disciplines of applied linguistics, namely sociolinguistics, anthropolinguistics, and psycholinguistics. In this article, the writer attempts to investigate the roles as well as the interconnection between these three disciplines of linguistics in multicultural preaching.